2022
DOI: 10.1002/ajb2.1862
|View full text |Cite
|
Sign up to set email alerts
|

Identification of key regulatory genes involved in the sporophyte and gametophyte development in Ginkgo biloba ovules revealed by in situ expression analyses

Abstract: Premise In Arabidopsis thaliana, the role of the most important key genes that regulate ovule development is widely known. In nonmodel species, and especially in gymnosperms, the ovule developmental processes are still quite obscure. In this study, we describe the putative roles of Ginkgo biloba orthologs of regulatory genes during ovule development. Specifically, we studied AGAMOUS (AG), AGAMOUS‐like 6 (AGL6), AINTEGUMENTA (ANT), BELL1 (BEL1), Class III HD‐Zip, and YABBY Ginkgo genes. Methods We analyzed thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…Gene expression analyses have clearly shown the expression of the ANT/AIL homologs in developing integuments in G. biloba (Wang et al, 2016;D'Apice et al, 2022), the conifer Pinus thunbergii (Shigyo and Ito, 2004;Yamada et al, 2008) and different species of Gnetum (Yamada et al, 2008;. Larsson et al and Schlögl et al showed the roles of the CUC homologs in regulating the differentiation of the shoot apical meristem (SAM) and embryogenesis in Picea abies (Larsson et al, 2012) and Araucaria angustifolia (Schlogl et al, 2012), respectively, as consistent with the roles in Arabidopsis (Chakraborty and Roy, 2019).…”
Section: Discussion Evolution Of the Core Regulatory Genes Associated...mentioning
confidence: 67%
See 2 more Smart Citations
“…Gene expression analyses have clearly shown the expression of the ANT/AIL homologs in developing integuments in G. biloba (Wang et al, 2016;D'Apice et al, 2022), the conifer Pinus thunbergii (Shigyo and Ito, 2004;Yamada et al, 2008) and different species of Gnetum (Yamada et al, 2008;. Larsson et al and Schlögl et al showed the roles of the CUC homologs in regulating the differentiation of the shoot apical meristem (SAM) and embryogenesis in Picea abies (Larsson et al, 2012) and Araucaria angustifolia (Schlogl et al, 2012), respectively, as consistent with the roles in Arabidopsis (Chakraborty and Roy, 2019).…”
Section: Discussion Evolution Of the Core Regulatory Genes Associated...mentioning
confidence: 67%
“…Larsson et al and Schlögl et al showed the roles of the CUC homologs in regulating the differentiation of the shoot apical meristem (SAM) and embryogenesis in Picea abies (Larsson et al, 2012) and Araucaria angustifolia (Schlogl et al, 2012), respectively, as consistent with the roles in Arabidopsis (Chakraborty and Roy, 2019). A strong expression of the BEL1 homolog has been detected in the integument in G. biloba D'Apice et al, 2022). The homologs of C3HDZ and ATS/KAN were expressed throughout ovule development in G. biloba D'Apice et al, 2022) and the Gnetum species (Zumajo-Cardona and Ambrose, 2021).…”
Section: Discussion Evolution Of the Core Regulatory Genes Associated...mentioning
confidence: 74%
See 1 more Smart Citation
“…Correlation between expression of the genes encoding adaxial/abaxial determinants and the leaf anatomy is ambiguous: in leaves of Abies holophylla composed of palisade and spongy mesophyll and in Picea smithiana with only spongy and no palisade mesophyll, an ARP homolog is expressed in a stripe between leaf margins (Du et al, 2020). YABBY expression marks entire young leaves of Pseudotsuga menziesii, A. holophylla, and P. smithiana (Du et al, 2020) despite their anatomical differences, but is confined to the abaxial leaf domain in G. biloba (Finet et al, 2016;D'Apice et al, 2022). Thus ARP, C3HDZ, YABBY and KANADI TFs did not gain the strict role in control of development of the ad/abaxial leaf domains in gymnosperms (Du et al, 2018(Du et al, , 2020.…”
Section: Wox3−regulated Marginal Meristem Appeared In Gymnospermsmentioning
confidence: 99%
“…After fertilization, the cone either enters a dormant state or undergoes rapid enlargement, which is crucial for seed production, plant reproduction, and seed yield in gymnosperms (Friedman, 2015;Kuhn et al, 2023). Despite its importance, our knowledge of cone development over the past century has largely been confined to gametophyte development and changes in anatomical structures observed in various species, including Ginkgo biloba, Araucaria angustifolia, and others (Florin, 1951;Owens & Moulder, 1977;Owens, 1984;Friedman, 2015;D'Apice et al, 2022;Elgorriaga & Atkinson, 2023;Kuhn et al, 2023). Over the past few years, the roles of several proteins potentially involved in cone development have been identified, including MADS-box, AGAMOUS-LIKE6, and CONSTANS-like proteins (Carlsbecker et al, 2013;Wang et al, 2020Wang et al, , 2022Yang et al, 2024).…”
Section: Introductionmentioning
confidence: 99%